2022
DOI: 10.3390/jof8030286
|View full text |Cite
|
Sign up to set email alerts
|

Two Cladosporium Fungi with Opposite Functions to the Chinese White Wax Scale Insect Have Different Genome Characters

Abstract: Insects encounter infection of microorganisms, and they also harbor endosymbiosis to participate in nutrition providing and act as a defender against pathogens. We previously found the Chinese white wax scale insect, Ericerus pela, was infected and killed by Cladosporium sp. (pathogen). We also found it harbored Cladosporium sp. (endogensis). In this study, we cultured these two Cladosporium fungi and sequenced their genome. The results showed Cladosporium sp. (endogensis) has a larger genome size and more gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
(82 reference statements)
0
6
0
Order By: Relevance
“…Cladosporium and Mucor species have recently been confirmed as important pathogens in hemipteran populations, with potential for biological control [85][86][87]. Unfortunately, during this study, we were unable to evaluate the pathogenicity of additional potentially pathogenic species such as these that that were isolated from dead L. delicatula.…”
Section: Discussionmentioning
confidence: 90%
“…Cladosporium and Mucor species have recently been confirmed as important pathogens in hemipteran populations, with potential for biological control [85][86][87]. Unfortunately, during this study, we were unable to evaluate the pathogenicity of additional potentially pathogenic species such as these that that were isolated from dead L. delicatula.…”
Section: Discussionmentioning
confidence: 90%
“…Using biological control technology to prevent and control diseases is effective. Cladosporium is a fungal genus widely distributed in natural environments in the form of endophytes, pathogens and saprophytes, which can infect and affect the yields and quality of host plants (Bensch et al, 2012; Liu, Yu, et al, 2022). The combination of morphological characteristics and phylogenetic analyses is an effective method to identify Cladosporium species (Sandoval‐Denis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified Cladosporium species as pathogens in various plant, animal and human hosts (Liu, Yu, et al, 2022; Nam et al, 2015; Wang et al, 2014). Interestingly, all of the species collected from diseased and healthy leaves of tea plants were not pathogenic when reinoculated, suggesting that these species are endophytes in tea plants.…”
Section: Discussionmentioning
confidence: 99%
“…were previously shown to vector plant pathogenic strains of F. oxysporum among cucumber plants in a greenhouse study [ 71 ]. Cladosporium taxa are also documented as common endophytes of plants [ 72 ] and have also been found in the human gut [ 73 ] and as both beneficial symbionts and pathogens of insects [ 74 , 75 ]. Consequently, while our results show that insect infestation does not substantially affect the fungal community structure of sorghum leaves and these insects likely do not gain many taxa from plants, the exchanges of Fusarium and Cladosporium taxa could affect plant and insect health.…”
Section: Discussionmentioning
confidence: 99%